Evaluation of antioxidant and tyrosinase inhibitory activities of the extracts of Sarcopoterium spinosum (L.) Spach fruits*. Issue 24 (17th December 2017) - Piras, Alessandra; Era, Benedetta; Di Petrillo, Amalia; González Paramás, Ana María; Maxia, Andrea; Maccioni, Alfredo; Porcedda, Silvia; Falconieri, Danilo; Rosa, Antonella
Abstract: Sarcopoterium spinosum fruits have been used to get extracts of different nature; two fixed oils were obtained by means of supercritical fluid extraction (SFE) with CO2 at 250 bar and 40°C and using n -hexane in a Soxhlet extraction (SE) apparatus. Aqueous solutions: an aromatic water (AW) and a residual water (RW) were obtained by hydrodistillation (HD). In the RW, following have been identified: quercetin glucuronide, luteolin 7- O -glucuronide, isorhamnetin 3- O -glucuronide, quercetin sulfate and quercetin. Among all tested plant extracts, the RW had the highest content of polyphenol (378 mg GAE/g of weight) and of flavonoids (26 mg QE/g of weight), and the highest antioxidant activity, comparable to that of Trolox. It was also the most active extract of this series (IC50  = 0.292 mg/mL) in the tyrosinase activity assays performed with L-3, 4-dihydroxyphenylalanine (L-DOPA) as substrate. Abstract :